AN ANALYSIS OF THE STUDENTS’ ERRORS IN USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT AT THE TENTH GRADE OF SMAN 2 BENGKALIS - Maisyara, Maisyara; Silvana, Ade; Fadli, Noval (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research described the students’ errors in using simple present in writing descriptive text. The research was conducted on June 2020. The subject of this research was the tenth grade students at SMAN 2 Bengkalis, and the object of the research were the studens’ errors in using simple present tense. The sample was taken based on simple random sampling technique with the total number were 34 students. In order to collect the data, the researcher used a test.The test was used to find out the students’ errors in using simple present tense in writing descriptive text. Based on the data analysis researcher concluded that the total errors of omission are 34 errors or 27.2%, errors of addition are 10 errors or 8.1%, error of misformation are 50 errors or 40,6%, and errors of misordering are 29 errors or 23.5%. Source of errors interlingual transfer was 29.2% and intralingual transfer was 70.7%. From the calculation of the data, error of misformation was the most frequent errors were made by the tenth grade students of SMAN 2 Bengkalis with the percentage 40.6%. The data also indicate that Intralingual transfer is the major source of the error were made by the students with the percentage 70.7%.